A Hands-on Simulation Game for Teaching Electronic Commerce : Final Report for a 1997 National Teaching Development Grant. - Swatman, Paula (Committee for University Teaching and Staff Development (CUTSD), 1997)
Final report of a National Teaching Development Grant at RMIT University, Interactive Information Institute. This project developed an innovative teaching tool called TRECS (Teaching Realistic Electronic Commerce Solutions). TRECS was designed to enhance student learning of Electronic Commerce (or e-Commerce) and the technologies which enable e-Commerce, including the Internet, electronic mail and Electronic Data Interchange (EDI). TRECS takes the form of a simulation game, where students operate a simplified, yet realistic, company by exchanging electronic business documents via the Internet with similar student organisations which can be located globally. The original TRECS concept had been trialed successfully with undergraduate Information Systems students for four years prior to the commencement of this project. These initial experiments also demonstrated the need for software tools to enhance the quality of the learning environment for students; and to automate operational tasks performed manually by TRECS facilitators. This project therefore involved the development of software and support tools and course integration materials, and the evaluation of this innovative teaching environment.